Contamination and characteristic of Ni and Cr metal on top soil from Antang landfill, Makassar City, South Sulawesi Province, Indonesia. (February 2019) - Artiningsih, A; Zubair, H; Imran, A M; Widodo, S
Abstract: Contamination and characteristic of Ni and Cr metals at the location of Antang Landfill Makassar City on topsoil have been investigated. Sample points are divided into four holes, two holes in the direction of groundwater flow (Hole A1 and Hole C1), two Hole perpendicular to groundwater flow (Hole B1 and Hole D1). Twelve samples (hole A1/3 samples; hole C1/3 samples; B1/3 samples dan D1/3 samples) were collected and analyzed using ICP-OES method, at a depth of 0 to 10 cm, 10 to 20 cm, and 20 to 30 cm respectively. This study aims to determine the characteristic of soil samples and to study the contamination of heavy metals (especially Ni and Cr) in the Antang Landfill, Makassar City, South Sulawesi Province, Indonesia. The results show that the concentration of Ni and Cr metals on Antang Landfill had spread horizontally, with varying amounts in every depth on the topsoil. The four site samplings of Landfill were hole A1, B1, C1 and D1 for each depth, containing heavy metals Ni and Cr, exceeding the threshold with exception of Cr metal for hole B1 at the depth of 10 to 20 cm and 20 to 30 cm in the range of 10 ppm (with regression value, r = 0.75), still on the threshold set by the government of the Republic of Indonesia and the directorate general of the supervision of drugs and food.